OSL chronologies of paleoenvironmental dynamics recorded by loess-paleosol sequences from Europe: Case studies from the Rhine-Meuse area and the Neckar Basin - Zens, Joerg; Schulte, Philipp; Klasen, Nicole; Krauss, Lydia; Pirson, Stephane; Burow, Christoph; Brill, Dominik; Eckmeier, Eileen; Kels, Holger; Zeeden, Christian; Spagna, Paul; Lehmkuhl, Frank (ELSEVIER, 2018)
Loess-paleosol sequences (LPS) represent an important terrestrial archive for the reconstruction of the paleoenvironmental evolution during the Last Glacial cycle in Europe. In the Rhine-Meuse area and the south-western Germany, there are only few numerical ages determined with state-of-the-art luminescence methods, which limits the robustness of established chronostratigraphies. This study presents a comparative dating approach using quartz and feldspar post-infrared (pIRIR(290)) optically stimulated luminescence (OSL) from fine- and medium-grained samples of five loess-paleosol sequences. Paleoenvironmental dynamics are reconstructed by high-resolution grain-size analysis. The OSL ages are evaluated as being robust and consistent with other records. Furthermore, we show that ages for hillslope deposits are sometimes overestimated due to low-frequency high-magnitude erosive processes. The integration of OSL ages, stratigraphy and high-resolution grain-size data contributes to a temporal more complete data record from Western and Central Europe. Secondly, we propose a combined stratigraphic model for LPS of the Last Glacial cycle, which is developed and discussed in the context of other key sites such as Havrincourt, Schwalbenberg II, Tonchesberg, Nussloch and Dolni Vestonice. Comparable chronologies and patterns in proxy data between sites with a large spatial distance suggest a possible semi-synchronous response to climatic changes in Europe. By combining our data with the Eifel-Laminated-Sediment-Archive (ELSA) and the NGRIP ice core, a relationship of loess archives and large-scale climatic signals is discussed and a proxydata based event-stratigraphy is developed. This model refines existing chronostratigraphic models and contributes to solve open discussion concerning the timing and demarcation of sedimentary units and sequences from for Western and Central Europe. (C) 2017 Elsevier B.V. All rights reserved.